A Techno-Economic study for heating poultry houses using renewable energy - ElZanaty, Heidi (AUC Knowledge Fountain, 2014)
In any broilers poultry house, fuel-based heating systems are commonly used to maintain the targeted temperatures for successful breeding of chicken. A considerable amount of fuel is consumed for this application, which leads to high running cost and contributes to the increase of air pollutant emissions. Given the current energy crisis and the urge to use renewable energy, this research studies the application of a solar heating system (SHS) for a poultry house. It includes the technical and economic study for the SHS and the integration of biogas produced from chicken manure as an auxiliary source of heat. The heating demand of a broilers poultry house of capacity 24000 birds located in Al Menia governorate in Egypt is calculated hourly over a complete year using TRNSYS simulation tool.Accordingly, a SHS is designed to cover part of this demand besides a fuel based auxiliary source. The system consists of: evacuated tubes, water storage tanks and fan coil units. The two main design variables of the SHS are the area of the solar collector (ASC) and the volume of the storage tanks (Vtank).An economical study of the SHS is carried out, where the net present value (NPV) is calculated. A solution space consisting of 65 different designs is explored, where the NPV is calculated at each solution to select the best economical design within the solution space. The calculation is performed twice, once using the Egyptian local fuel price, where the SHS is found to be economically feasible using certain designs only.The other calculation is performed using the international minimum benchmark price of diesel fuel, where the NPV of all designs is found to be significantly higher and thus, the use of SHS is more appealing at this fuel price.Other parameters such as the infiltration rate of the building and the usage of latent heat storage technique are examined to explore their effect on the performance of the SHS. Finally,an all-green heating solution is introduced, where bio-digesters are used to produce biogas from the waste of the poultry house in order to complement the SHS by covering the auxiliary energy needed. The economics of the all-green solution is examined and found to be bettered.